Réponses

2014-09-14T21:57:55+02:00
A) 4x + 11 = 2x + 15
4x - 2x = 15 - 11
2x = 4
x = 4/2
x = 2

b) 3x + 2 = 2x - 5
3x - 2x = - 5 - 2
x = - 7

c) 5x - 3 + x - 5
5x + x - 3 - 5 = 0
5x + x = 3 + 5
6x = 8
x = 8/6

d) 7x + 5 = 3x + 2

7x - 3x = 2 - 5
4x = - 3
x = - 3/4
x = - 0,75
Meilleure réponse !
  • Utilisateur Brainly
2014-09-14T21:58:56+02:00
4x + 11 = 2x + 15
4x - 2x = 15 - 11
2x = 4
x = 4/2
x = 2

3x + 2 = 2x - 5
3x - 2x = - 5 - 2
x = - 7

5x - 3 = x - 5
5x - x = - 5 + 3
4x = - 2
x = - 2/4
x = - 1/2

7x + 5 = 3x + 2
7x - 3x = 2 - 5
4x = - 3
x = - 3/4